Deliverable D5.12 iAOS portal with user manual V2 - Hamre, Torill; Monsen, Frode; Richard, Gaetan; Pirazzini, Roberta; Luy, Goukun; Ors, Fabien; Renard, Didier; Storheim, Espen; Aarnes, Øyvin; Solgaard, Anne; Voss, Peter; Andersen, Ole B.; et al. (Zenodo, 2022)
The INTAROS project develops an integrated Arctic Observation System (iAOS) by extending, improving and unifying existing systems in the different regions of the Arctic. Within INTAROS, WP5 (Data integration and management) develops the iAOS Portal, which provides access to selected datasets and services offered by INTAROS partners and by other Arctic data providers and service providers. This document describes the major functionality and features of this portal and how it has been implemented. Required functionality has been identified through dialogue with users and stakeholders. The approach has been to use agile development techniques to quickly refine user needs and implement new features iteratively. Two main categories of users of the portal were identified: (1) data/service providers and (2) data/services consumers. Providers make their data or services available through the portal, and update the descriptions of these if changes are made. Consumers search for and access data or services, with sufficient descriptions (metadata) for both data and services to whether to use them in their work. The population and promotion of the iAOS Portal equally depends on data providers and consumers including service providers. The iAOS Portal has been implemented using a leading data management system framework named CKAN (Comprehensive Knowledge Archive Network). CKAN offers a broad range of the needed features out of the box and has an active community that develops additional features (plugins) that can be added to the iAOS Portal as needed. Using the CKAN core components and mature plugins, we have implemented the following main components of the iAOS Portal: INTAROS Data Catalogue , holding descriptions (metadata) of datasets collected or generated with support from INTAROS. iAOS Portal Data Catalogue , holding metadata harvested from other catalogues offering relevant dataset for the applications under development in WP 6 of INTAROS. Services and Applications , describing services and applications developed in ...